2019
DOI: 10.1021/acsomega.9b02425
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Interactions Between Charged Surfactants and Ionic Poly(amino acids) by Isothermal Titration Calorimetry

Abstract: Interactions between charges play a role in protein stability and contribute to the energetics of binding between various charged ligands. Ionic surfactants are charged molecules, whose interactions with proteins are still rather poorly understood despite their wide applications. Here, we show by isothermal titration calorimetry that cationic alkylammonium surfactants bind to negatively charged polyaspartate and polyglutamate homopolymers stoichiometrically, i.e., one surfactant molecule per charged amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…55,56 For polymers bearing cationic quaternary ammonium groups, endothermic events are observed for titration of PFOA into solutions of both PAO-F + (first injection) and PA+ (first three injections) (Figures 7, in red and gray), indicating the presence of an endothermic event arising from the electrostatic attraction between PFOA and the two cationic polymers. This is in line with the report by Skvarnavicíus et al, 57 who observed endothermic binding interactions by titrating cationic alkylamines surfactant solution into a solution containing anionic poly(amino acid)s with carboxyl groups.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…55,56 For polymers bearing cationic quaternary ammonium groups, endothermic events are observed for titration of PFOA into solutions of both PAO-F + (first injection) and PA+ (first three injections) (Figures 7, in red and gray), indicating the presence of an endothermic event arising from the electrostatic attraction between PFOA and the two cationic polymers. This is in line with the report by Skvarnavicíus et al, 57 who observed endothermic binding interactions by titrating cationic alkylamines surfactant solution into a solution containing anionic poly(amino acid)s with carboxyl groups.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…Skvarnavicius [ 28 ] presented another experimental observation about the difference between sulfate and sulfonium groups. The authors measured the enthalpies by isothermal titration calorimetry of cationic poly(amino acid)s with negatively charged alkyl sulfates and alkane sulfonates.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35 ] Even though, chromatography is the method of choice for plasma fractionation, there is still a need for optimization of the production processes for increased economic benefits and safety. [ 28 ] Biopolymers with sulfate‐based ligands, mostly Heparin Sepharose, are used in these polishing steps, especially for production of both recombinant and plasma derived clotting factor IX, and possible introduction of more stable and virus‐safe substitutions for this resin have been frequently discussed. [ 19,20,35,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…As denaturation and unfolding of protein depend on the pH of the medium, , the micelle formation of surfactants is also affected by the pH of the solution. It has been observed that at low pH and concentration, the interactions between amino acids and surfactants are mainly electrostatic, and the interactions become hydrophobic with an increase in the concentration of surfactants. , Further, at low pH, amino acids become cationic, and at high pH, they behave as zwitterions/anionic . Numerous surfactants have been studied, and it has been shown that pH has no impact on aggregations. , However, amino acids are neutral when the pH is near to the isoelectric point.…”
Section: Effect Of Physical Parameters On Amino Acid–surfactant Inter...mentioning
confidence: 99%